Bepotastine besilate for the treatment of perennial allergic rhinitis. (13th October 2018) - Carrillo-Martin, Ismael; Gonzalez-Estrada, Alexei; Dimov, Ves
ABSTRACT: Introduction : Bepotastine besilate (BB) is a second-generation H1-antihistamine that, as an ophthalmic solution, is approved in the United States by the Food and Drug Administration (FDA) for the treatment of allergic conjunctivitis. In other countries, the oral presentation of BB is widely used for the improvement of symptoms of allergic rhinitis (AR) as well as urticaria and chronic pruritus with results similar to those by other drugs of the same class. Areas covered : This article was created from a comprehensive literature search with information taken from clinical trials. The articles that have been selected evaluate the clinical and non-clinical pharmacology of BB as well as its use in AR and its efficiency in the improvement of symptoms, its safety, common adverse effects, and overall experiences of its use. Expert opinion : BB is effective and well-tolerated in the treatment of allergic rhinitis. Side effects are infrequent in patients with AR who do not have kidney or liver disease. Clinical trial experience with oral bepotastine outside the United States has confirmed its safety. BB can be useful as a therapeutic option in patients with AR who would like to explore an alternative to the currently available once-daily oral H1-antihistamines.